Determination of significant factors of landslide processes and flooding - Katkov, Mykhailo; Malovanyy, Myroslav; Kotsiuba, Iryna; Senchuk, Tetyana; Lavinda, Maryna (Видавництво Львівської політехніки, 2020)
The linear dependence of some geological (significant) factors responsible for landslide and flooding processes on the cost of geotechnical surveys determining these factors was proved. The principle of selection of engineering-geological surveys, which assess the factors of occurrence of landslide and flooding with high probability, was developed. The possibility of identifying economic territories that may be susceptible to landslide and flooding processes based on already existing basic data of previously conducted engineering-geological surveys is substantiated. A preproject (planned) method of calculating the costs of geotechnical surveys based on the existing basic data is proposed.
Keywords: landslides; floods; significance of factors; linear regression dependence; geological engineering surveys; cost